Peran Promotional Mix Dalam Membentuk Brand Image Produk City Car di Kota Pekanbaru (Studi Kasus pada Honda Brio) - Monina Selfi Karlina; Aida Nursanti; Tengku Firli Musfar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of this research is to examine the role of promotional mix variables which consist of advertising, personal selling, sales promotion, public relations, and direct marketing towards brand image of Honda Brio car in Pekanbaru. Sample’s selection that used with the method of non-probability sampling. Selected sample is consumer who uses Honda Brio car, specifically who lives in Pekanbaru city, ever been involved in Honda Brio’s promotional mix activity, and the consumer that considered mature enough (about 20 years old) to fill the questionnaire. The data analysis that used is multiple regression linear analysis which use SPSS version 20. The result indicates simultaneously that advertising, personal selling, sales promotion, public relations and direct marketing have a significant effect towards brand image of Honda Brio car in Pekanbaru, whereas partially, not all of each promotional mix variables have significant effect towards brand image of Honda Brio car in Pekanbaru. Only advertising, personal selling, sales promotion, and public relations that have significant effect towards brand image of Honda Brio car in Pekanbaru, and the most dominant variable or the most powerful variable is public relations.Keywords: Promotional mix, advertising, personal selling, sales promotion, public relations, direct marketing, and brand image.